The The Impact of Macroeconomic and Specific Factors of Commercial and Islamic Banks on Profitability Evidence from Egyptian Market - Abdelzaher, Mai Ahmed (International Journal of Economics and Financial Issues, 2022)
The purpose of this research paper is to analyze the effectiveness of the economic factors affecting Islamic and commercial banks during the Egyptian financial crisis from 2003 to 2019. A sample was taken from eleven banks registered in the Egyptian financial market, and the data were collected on an annual basis. The variables are as follows: return on assets (ROA); return on equity (ROE); reinvestment rate; size; nonperforming loans; operating leverage; loan growth; inflation rate; GDP; and deposit growth. Several statistical methods were used, such as a normality test, descriptive statistics, a t-test, and a group unit root. A panel data analysis was also applied to compare data from Islamic and commercial banks. The data revealed a negative relationship between the type of bank and ROA and ROE as well as a positive relationshipbetween the global financial crisis and the banks’ ROE and ROE.